Investasi dalam Perspektif Islam: Analisis Prinsip, Instrumen, dan Tantangan Kontemporer - Bela Bela; Ichsan Iqbal (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Investment from an Islamic perspective represents an economic activity that extends beyond financial gain by incorporating spiritual values, ethical considerations, and social responsibilities grounded in Sharia principles. The rapid growth of the Islamic financial industry has increased public interest in various investment instruments that comply with Islamic law. A qualitative approach based on library research was employed through the examination of relevant primary and secondary sources, including the Qur’an, Hadith, fatwas issued by the National Sharia Council of the Indonesian Ulema Council, academic books, scientific journals, and reports from related institutions. The analysis utilized content analysis and thematic analysis techniques to identify the fundamental principles of Islamic investment, the development of available investment instruments, and the contemporary challenges associated with their implementation. The findings indicate that Islamic investment is founded on the principles of justice, public welfare, transparency, and the prohibition of riba (usury), gharar (excessive uncertainty), and maysir (gambling or speculation). Various Islamic investment instruments, including Sharia-compliant stocks, sukuk, Islamic mutual funds, and Islamic deposits, have experienced significant growth in Indonesia. Nevertheless, low levels of Islamic financial literacy, limited product innovation, governance issues, and the rapid advancement of financial technology continue to pose substantial challenges. Strengthening regulatory frameworks, enhancing public education, and promoting sustainable product innovation are essential for supporting the development of an inclusive and sustainable Islamic investment ecosystem.